The virtual currency : its risk and legality Bitcoin as a model - lasnouni, hafida; belhadef, rahma; Ghoual, Nadai (Finance and Business Economies Review, 2020)
Through this study, we seek to identify the most important risks resulting from dealing in virtual currencies, whether financially or monetarily , and we concluded at the end of the study that the increased prevalence of the use of virtual currencies, especially Bitcoin, will lead in the future to change the methods of the global financial sector Perhaps it presents increasing challenges, as a chapter on its extreme danger to its dealers, given that it is not guaranteed and has fluctuating value in the short term, and it also contributes to supporting illegal trade. This has made this currency a suspicion in many countries that have prevented and even criminalized dealing with it to limit its use Only for certain countries.